Fingerprint Angles and Patterns in the Population of Najaf Province - Hussein, I. A; Abdullah, N.F (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The values of fmgerprint angles were studied in 57 females and 44 males from Najaf province in the m iddle of Iraq. Some results of tlus sample were compared with the results of Southern provinces sample from Iraq i population. The rCS lts revealed that the mean of maximum fingerprint angle (MFA) and also the mean of absolute fingerprint angle (AFA) between samples in the studied provinces did nnt differ significantly. However, the unilateral analysis revealed only one significant diOerence in LS of the male samples (r-2.89, P<O.Ol), while the bilateral analysis revealed two significant differences, wluch occurred in Rl and R3 of the right hand. As lbr the compari son between sexes of the sampl e in N af province, the unilateral analysis revealed a significant difference in LS, but there wasn’t a significant difference in (MFA). The bilateral analysis of Southern provinces sample showed significant differences in Rl and R3 as well as in (AFA). The frequency distribution for (MFA) and (AFA) reveals that the males of Najaf sample have a narrow range in these two variables in comparison with the males of Southern provinces sample, whilst the female sample of Najaf province has a narrow range for (AFA) values only. Latter, a positive relationship was found between Pattern Intensity Index (PII), percentage of whorls and the AFA val ues. This study shed the light on the importance of digital fingerprint angle values when analyzed at the level of separate fingers in detecting genetic variation betwee.n samples and sexes, but not at the level of summation the values of all fingers together.